VIRALNYA SKINCARE MASKER ORGANIK NON BPOM, PERLINDUNGAN KONSUMEN MULAI DIPERTANYAKAN - Putri, A.A.Ayu Eugene Satya; Pramana Putra, Made Aditya (Kertha Wicara : Journal Ilmu Hukum, 2023)
The purpose of this study is first one, namely to increase knowledge related to the analysis of consumer protection for the distribution of non-BPOM organic face masks that are sold on various e-commerce platforms. Second, to add insight regarding the sanctions received by sellers who market non-BPOM organic face masks. Third, to increase knowledge regarding the form of supervision from BPOM regarding non-BPOM organic facial mask products. Utilising normative legal research techniques, this investigation. A legal approach in the form of legislation and an analytical approach are the two approaches used. In this study, it is demonstrated how consumer protection can take both preventive and repressive forms. Then, the Law No. 8 of 1999 Concerning Consumer Protection regulates the accountability of merchants who have damaged customers by marketing non-BPOM organic face masks in Article 19 paragraph (1). Additionally, the sanctions received by business actors as sellers refer to Law No. 8 of 1999 regarding Consumer Protection Article 62 paragraph (1), PP RI No. 80 of 2019 regarding PMSE 17 paragraph (1), and Republic of Indonesia Presidential Regulation No. 80 of 2017 regarding BPOM Article 4 letter a. Additionally, there is a type of BPOM monitoring pertaining to the distribution of non-BPOM organic face masks. This type of supervision is explained in Presidential Regulation No. 80 of 2017 about BPOM Article 3 paragraph (1) part d. Key Words: Organik Face Mask, Consumer Protection, Non BPOM